Mobile Banking Services : Security, Guarantee And Service Credibility On Customer Satisfaction Of Bank Syariah Indonesia - Nurudin; Nur Huda; Muhammad Dinu Nasoihul Umam (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2022)
The purpose of this study was to determine the effect of security relationships, guarantees, credibility on customer satisfaction. The total population in this study was 1,939 students with a sample of 96 FEBI student respondents from the 2017-2020 UIN Walisongo Semarang. The research data is in the form of quantitative data with data analysis techniques using SPSS tools. The results showed that the security variable had no significant effect on customer satisfaction, the guarantee variable had no significant effect on customer satisfaction, while the credibility variable had a significant effect on customer satisfaction.